PHYSICAL OVERSTRAIN IN SPORTS: MODERN PREVENTION AND REHABILITATION PROCEDURE - Lutkov, V.F.; Miller, L.L.; Smirnov, G.I.; Shadrin, D.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze exposures to the microtraumatic disease risks and benefits of Traumel-C for treatment of the microtraumatic-disease-associated impaired local circulation in gorodki players, to facilitate trainings and special fitness improvement efforts. Methods and structure of the study. We sampled for the study Masters of Sport in gorodki (n=12) [national game similar to skittles, with pins knocked out by throwing a bat]. The sample was tested for microcirculation disorders in the upper limbs by an infrared thermometric DT-639 system, with the pain syndrome self-rated on a visual-analog scale. The detected microcirculation disorders were treated by Traumel-C antihomotoxic medication (made by Heel Co.) with taping. Results and conclusion. To identify the injury risk factors for gorodki players, we first surveyed their coaches (n= 24). They reported the following common risk factors: idle periods in trainings followed by excessive physical workouts (21%) and mismanagements in combining the training elements (11%); and the following sport-specific risk factors: elbow joint overextensions (32%), and too heavy bats favored by the sport elite (29%). The surveys identified the core musculoskeletal system chronic overstrain risk factors for the gorodki sport sample and showed benefits of the biological regulation service using te hTraumel-C antihomotoxic medication for the upper-limb microcirculation protection, improvement and post-training rehabilitation purposes. We recommend Traumel-C with taping for application in the gorodki training systems for the upper-limb musculoskeletal system overstrain prevention and sport-specific fitness improvement purposes.